2019
DOI: 10.3390/ma12121995
|View full text |Cite
|
Sign up to set email alerts
|

Study on Tensile Properties of CFRP Plates under Elevated Temperature Exposure

Abstract: Elevated temperature exposure has a negative effect on the performance of the matrix resin in Carbon Fiber Reinforced Plastics (CFRP) plates, whereas limited quantitative research focuses on the deteriorations. Therefore, 30 CFRP specimens were designed and tested under elevated temperatures (10, 30, 50, 70, and 90 °C) to explore the degradations in tensile properties. The effect of temperature on the failure mode, stress-strain curve, tensile strength, elastic modulus and elongation of CFRP plates were invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…A similar change in the typical fracture of CFRP specimens during longitudinal tensile tests with increasing temperature was observed in works [7,8].…”
supporting
confidence: 79%
See 2 more Smart Citations
“…A similar change in the typical fracture of CFRP specimens during longitudinal tensile tests with increasing temperature was observed in works [7,8].…”
supporting
confidence: 79%
“…In [6], the effect of elevated temperatures on the mechanical characteristics of polymer composites was analyzed from the known literature sources, and it was shown that at temperatures below the glass transition temperature T G , there is a slight degradation of their strength, but when reaching and exceeding T G temperature, the strength and rigidity fall sharply. Furthermore, as the temperature increases, accompanied by a sharp change in the properties of the plastic and its ablation, the typical character of fracture of unidirectional CFRPs changes from catastrophic explosive at room temperature to the gradually scattered fracture of carbon fibers [7,8].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Carbon Fiber-Reinforced Polymer (CFRP) with great material performance has been widely applied in various aspects after its invention, and its mechanical properties have also been extensively studied (Kalavagunta et al, 2014;Barile et al, 2019;Zhang et al, 2019;Yang et al, 2019;Yuan et al, 2019;Saleem et al, 2019). As an effective alternative to traditional materials for strengthening and repairing damaged structures, CFRP-reinforced bridge structure has been extensively investigated (Lu et al, 2018;Peng et al, 2014;Hosseini et al, 2019;Shukri et al, 2018;Mashrei et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Carbon fiber reinforced polymer composites (CFRPs) are widely used in the industry due to their excellent mechanical properties and good corrosive resistance [1,2]. In particular, they are commonly used in aeronautical and aerospace industries in the manufacturing of aircrafts, ships, space shuttles, and more.…”
Section: Introductionmentioning
confidence: 99%